2023
DOI: 10.1186/s13012-022-01253-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing postpartum haemorrhage detection and management and the implementation of a new postpartum haemorrhage care bundle (E-MOTIVE) in Kenya, Nigeria, and South Africa

Abstract: Background Postpartum haemorrhage (PPH) is the leading cause of global maternal deaths, accounting for 30–50% of maternal deaths in sub-Saharan Africa. Most PPH-related deaths are preventable with timely detection and initiation of care, which may be facilitated by using a clinical care bundle. We explore influences on current PPH detection and management and on the future implementation of a new PPH bundle (E-MOTIVE) in low-resource, high-burden settings. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
12
1
1
Order By: Relevance
“…This research found that obstetricians were unaware of E-MOTIVE bundle of care for PPH management, however, current PPH management already includes all individual components of E-MOTIVE in Pakistan. Our ndings are contrary to other studies conducted in Kenya, Nigeria and South Africa (34,35), where HCPs were familiar with this bundle of care. The reasons may include the limited training opportunities,…”
Section: Acknowledgmentscontrasting
confidence: 99%
See 3 more Smart Citations
“…This research found that obstetricians were unaware of E-MOTIVE bundle of care for PPH management, however, current PPH management already includes all individual components of E-MOTIVE in Pakistan. Our ndings are contrary to other studies conducted in Kenya, Nigeria and South Africa (34,35), where HCPs were familiar with this bundle of care. The reasons may include the limited training opportunities,…”
Section: Acknowledgmentscontrasting
confidence: 99%
“…Lack of training of the HCPs, risk factor screening, timely diagnosis, volume administration, blood transfusion and hospital infrastructure were some barriers in PPH detection and management reported in this study. Although the WHO recommends the appointment of well trained staff to prevent and manage the PPH (31), the shortage of well-trained healthcare staff is global challenge but it is intensi ed in LMICs including Pakistan (13,20,21,31). Only one respondent of this study attended an awareness session conducted by an institution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alkema et al,2017;Daemers et al, 2017, Forbes et al, 2023 Lodeka, 2017; Makin-Zimaliran et al, 2022); poor service delivery important factors in uencing midwives' implementation of the guidelines included a non-conducive environment, a lack of support, autonomy, and empowerment(Simona et al, 2023; Petterson, (2018), and poor role de nition, delegation, and supervision(Maaløe et al,2021). Poor health conditions, burnout, nancial struggles, and disregard from public and health teams were also identi ed(Simona et al, 2023; Petterson, 2018), as well as a lack of training, education, orientation, and poor adaptation to midwifery education(Forbes et al, 2023; Solnes mitten et al, 2017; Petterson, 2018).…”
mentioning
confidence: 99%